Soft Skills for a Successful Engineering Graduate Career - A. P. Isaev; L. V. Plotnikov (Высшее образование в России)
This article focuses on soft skills that are needed for young engineers starting their professional careers. The objectives of the study were: 1) to determine soft skills of young engineers that are most in demand among employers; 2) to assess the importance of soft skills for the successful start of the graduates’ professional career; 3) to determine the necessary conditions for soft skills development in the engineering bachelor’s degree educational process. The methods of expert assessment, written survey, oral conversation, decomposition, statistical and structural-logical analysis were used in the study. A review of foreign and domestic studies focusing on the analysis and assessment of soft skills needed in the work of engineering and technical personnel in various fields of activity is made. The results of an empirical study showed which soft skills are assessed by young engineers and heads of industrial enterprises as highly demanded for university graduates’ successful career start. On their basis, an optimal grouping of soft skills was compiled, which meets the requirements of professional training for many types of engineering activities. The authors adduce the results of a comparative analysis of the highlighted soft skills, based on the assessments of their importance made by teachers of engineering disciplines, heads of departments and engineers of industrial enterprises, as well as senior students of engineering bachelor’s degree. It was found that representatives of industrial enterprises, especially managers more highly assess the importance of soft skills for the successful professional activity of graduates of an engineering university in comparison with teachers and students. An explanation of the discrepancies in the obtained assessments of soft skills is proposed. The difficulties and necessary conditions for soft skills development in engineering bachelor degree educational process are determined. The article substantiates the key role of the studentcentered approach to teaching and the corresponding teaching and learning technologies for the successful development of soft skills on the basis of different disciplines, including specialized and practice-oriented ones for the engineering profile. The authors formulate the conclusions about the features of soft skills development, which can be used to improve the university training of engineering personnel.